2010
DOI: 10.3146/ps09-025.1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Late Season Glyphosate Applications on Peanut (Arachis hypogaea) Seed Development and Germination

Abstract: Field studies were conducted to determine runner type peanut response to glyphosate at 80, 160, 240, 320, and 470 g ae/ha applied 75, 90, and 105 days after planting (DAP) at Plains and Ty Ty Georgia in 2006 and 2007. Data collected included seed kernel mass, peanut pod yield, and seed germination. The two-way interaction between DAP and glyphosate rate was not observed for any variable. Data indicated that glyphosate applied at 75 DAP reduced peanut seed mass to 643 mg/kernel, which was less than the 90 or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…across the southeast (Lassiter et al, 2007;Prostko et al, 2011;Prostko et al, 2013). A large percentage of cotton and soybean cultivars have herbicide resistance technology to assist in weed management, and the increased use of glyphosate and glufosinate herbicides throughout the growing season increased the occurrence of accidental injury to peanut crops (Grey and Prostko, 2010;Johnson et al, 2012a;Lassiter et al, 2007). When spray systems are not properly cleaned prior to other applications to different crops, crop injury can occur from herbicide residue remaining in the spray system (Grey and Prostko, 2010;Prostko et al, 2011).…”
mentioning
confidence: 99%
“…across the southeast (Lassiter et al, 2007;Prostko et al, 2011;Prostko et al, 2013). A large percentage of cotton and soybean cultivars have herbicide resistance technology to assist in weed management, and the increased use of glyphosate and glufosinate herbicides throughout the growing season increased the occurrence of accidental injury to peanut crops (Grey and Prostko, 2010;Johnson et al, 2012a;Lassiter et al, 2007). When spray systems are not properly cleaned prior to other applications to different crops, crop injury can occur from herbicide residue remaining in the spray system (Grey and Prostko, 2010;Prostko et al, 2011).…”
mentioning
confidence: 99%
“…Research has indicated that peanut injury from glyphosate at 240, 320, and 470 g ai ha 21 caused significant yield reduction of 12 to 36% when applications were made 75, 90, and 105 days after planting (DAP) (Grey and Prostko, 2010). In another study, glyphosate applied to peanut at 560 g ai ha…”
mentioning
confidence: 99%
“…Peanut is commonly grown in the proximity of cotton and soybean across the southeast (Lassiter et al, 2007;Prostko et al, 2011;Prostko et al, 2013). Herbicide resistance technology is used in most cotton and soybean cultivars for weed management solutions, and the increased use of glyphosate and glufosinate herbicides throughout the growing season increased the occurrence of accidental injury to sensitive crops like peanut (Grey and Prostko, 2010;Johnson et al, 2012a;Lassiter et al, 2007). Peanut foliage injury can occur from herbicide residue remaining in the spray system when it is not properly cleaned prior to the next application in peanut (Grey and Prostko, 2010;Prostko et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When glyphosate was applied to peanut plants at 28 days after planting (DAP), rates of 280 g/ha or higher caused significant yield reductions (Lassiter et al 2007). When applied between 75 to 105 DAP, glyphosate at 240, 320, and 470 g/ha reduced peanut yield by 12%, 24%, and 36%, respectively (Grey and Prostko 2010). Estimated peanut yield losses for dicamba applied at rates between 40 to 560 g/ha at 30, 60, or 90 DAP ranged between 2 and 100% (Prostko et al 2011).…”
mentioning
confidence: 99%